2021
DOI: 10.1038/s41438-021-00647-3
|View full text |Cite
|
Sign up to set email alerts
|

Tomato genomic prediction for good performance under high-temperature and identification of loci involved in thermotolerance response

Abstract: Many studies showed that few degrees above tomato optimum growth temperature threshold can lead to serious loss in production. Therefore, the development of innovative strategies to obtain tomato cultivars with improved yield under high temperature conditions is a main goal both for basic genetic studies and breeding activities. In this paper, a F4 segregating population was phenotypically evaluated for quantitative and qualitative traits under heat stress conditions. Moreover, a genotyping by sequencing (GBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 93 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…A comprehensive understanding of the molecular mechanisms that determine the relationships between important agronomic traits will help further promote breeding techniques and research to shape tomato plasticity under high temperature stress [ 13 ]. The frequent occurrence of global temperature extremes has also greatly upset the balance of carbon dioxide metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A comprehensive understanding of the molecular mechanisms that determine the relationships between important agronomic traits will help further promote breeding techniques and research to shape tomato plasticity under high temperature stress [ 13 ]. The frequent occurrence of global temperature extremes has also greatly upset the balance of carbon dioxide metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Cappetta et al evaluated the phenotypic characteristics of quantitative and qualitative traits by applying heat stress treatment to self-crossing F4 segregated populations of heat tolerant tomato varieties, and predicted several potential loci that may be involved in high temperature response by calculating the effect of a single nucleotide polymorphism (SNP)-dependent variation and combining with quantitative trait locus (QTL) analysis. This, to some extent, reveals a genome-selective (GS)-dependent approach that can control interactions between plants and high temperatures [ 13 ]. Lu and colleagues then found that after exposure to extreme heat and moderate warming, mutation rates of single-nucleotide variations (SNVs) and small indoles were increased in Arabidopsis thaliana multigenerational accumulation plants, which is associated with changes in epigenetic modifications, such as DNA methylation levels [ 18 ].…”
Section: Emerging Strategies In Vegetable Practice Managementmentioning
confidence: 99%
See 3 more Smart Citations